Pengaruh Penggunaan Mixing Foundation dengan Teknik Bakar Terhadap Kulit Wajah Bekas Jerawat Bopeng - Deana, Annisha Amelya Putri; Hannum, Lili Faridah; Dewi, Siska Miga (Universitas Negeri Jakarta, 2023)
The foundation mixing technique is a development in facial makeup techniques. One technique so that the mixed foundation is evenly mixed is to use the foundation burn technique. This can help maximize foundation mixing and cover problematic parts of the face to make it look more perfect. These two techniques can produce long-lasting and smoother facial makeup results. The aim of this research is to determine the effect and comparison of the results of mixing foundation with the burning technique and the results of mixing foundation without the burning technique. The method used in this research is True Experimental. Data analysis techniques Normality Test, Homogeneity Test, t Test and Duncan Test. The results of the analysis show that there is an effect of using mixed foundation without burning technique on the durability indicator X1 (2.28) which is significantly different from mixing foundation with burning technique X2 (3.85). The results of the analysis of the effect of using mixed foundation without burning techniques on the covering power indicator X1 (2.85) are significantly different from mixing foundations using burning techniques X2 (3.14).